Direct Entry to Erythronlolides via a Cyclic Bis[Allene] - Liu, Kai (2011)
The complexity and low tractability of antibiotic macrolides pose serious challenges to addressing the problem of resistance through semi- or total synthesis. Here we describe a new strategy, the preparation of a complex, yet tractable, macrocycle, and the transformation of this macrocycle into a range of erythronolide congeners. These compounds represent valuable sectors of erythromycinoid structure space and constitute intermediates with the potential to gain further purchase in this space. The routes are short. The erythronolides were prepared in three or fewer steps from the macrocycle, which was prepared in a longest linear sequence of 11 steps.